Peran Perencanaan Pajak, Beban Pajak Tangguhan, dan Leverage dalam Manajemen Laba: Studi Empiris pada Perusahaan Consumer Non-Cyclical di BEI (2018-2022) - Cendana, Imelda; Purwatiningsih, Purwatiningsih (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this research is to see the influence of Tax Planning, Deferred Tax Burden, and Leverage on Profit Management in companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. 113 Non Cyclical Consumer Companies listed on the BEI from 2018 until 2022 is the study population. Purposive sampling was used in the sample selection process, and a sample of 19 businesses was obtained using 95 sets of observation data. Secondary data that uses a quantitative approach is the data source. Descriptive statistical analysis and multiple regression analysis were used. utilize the E-views Version 9 application to process data. Based on the test results, this research states that simultaneously Tax Planning, Deferred Tax Expenses and Leverage influence Profit Management. Partially, Tax Planning has an effect on Profit Management, Deferred Tax Expenses have no effect on Profit Management, and Leverage has no effect on Profit Management.